Understanding quality of life in children with asthma and their parents: Family resources and challenges - Crespo, Carla (2011)
The present research investigated the links between caregiver burden, family environment, and quality of life in 97 pairs of children with asthma and one of their parents (the primary family caregiver). Using structured equation modelling, within-participant analyses showed that family environment was positively linked to quality of life for both children and parents respectively. Across-participant analyses demonstrated that parents’ positive perceptions of family environment were associated with parents’ and children’s improved quality of life. In addition, parents’ perceptions of family environment mediated the link between caregiver burden and parents’ and children’s quality of life. Implications for intervention with families are discussed in light of this study’s important results.